International Stock Returns and Market Integration : A Regional Perspective - Del Negro, Marco (IMF Working Papers; Working Paper ;, 2002)
We investigate the relative importance of country and industry effects in international stock returns, with the innovation that we decompose country effects into region and within-region country effects. We divide the global stock market into the Americas, Asia, and Europe and find that most of the variation explained by country effects is actually due to region effects. Over time, these region effects have fallen. Within regions, however, only in Europe has segmentation declined, while it has increased elsewhere. Europe is also the only region where industry effects are now robustly more important than country effects.